Article RETRACTED due to manipulation by the authors Analysis of Multiple Intelligence of Elementary Students in Physical Education Lessons in Yogyakarta Indonesia - Ismail Gani; Tomoliyus Tomoliyus; Awan Hariono; Ratko Pavlovic; Arief Darmawan; Abdul Aziz Purnomo Shidiq; Muhammad Imam Rahmatullah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The application of learning based on multiple intelligences has implications for collective awareness about diversity, uniqueness and equitable education. The objective of this study is to describe the level of multiple intelligences of students learning physical education in elementary schools, as well as to identify differences in the levels of each type of multiple intelligences based on the gender of the students.This study is a descriptive and comparative quantitative study. Purposive sampling was used to collect the samples. The 124 respondents included 57 male and 67 female students from Yogyakarta’s Syuhada Mosque Elementary School. The instrument employs a questionnaire comprised of 21 statements derived from the substance of multiple intelligences. The instrument employs a Likert scale of 1 to 4. The instrument was developed using theory, with expert consultation, and its validity and reliability were tested. Descriptive statistical data analysis used frequency distribution to describe the state of multiple intelligences, and non-parametric Mann-Whitney Test analysis used to determine differences in multiple intelligences based on gender. Based on the frequency distribution analysis, it was determined that the highest frequency of intelligence corresponds to the following criteria: the "low" category is in logical-mathematical (22.58%), the "moderate" category is in visual spatial (40.32%), the "high" criterion is in intrapersonal (58.06%), and the "very high" category is in bodily-kinesthetic (54.03%). According to the Mann-Whitney Test analysis, The value of Sig > 0.05 indicates that the hypothesis that elementary school male and female students learn physical education differently in terms of their multiple intelligences (musical, verbal linguistic, intrapersonal, visual spatial, interpersonal, bodily-kinesthetic, logical-mathematical) is rejected. Meanwhile, the hypothesis that male and female students have different levels of naturalist intelligence when learning physical education in primary schools is accepted because the Sig < 0.05. Elementary school students' levels of each type of multiple intelligence in physical education are quite variable. The Mann-Whitney Test analysis revealed that there was no significant difference in the level of multiple intelligences (musical, verbal-linguistic, intrapersonal, visual-spatial, interpersonal, bodily-kinesthetic, logical-mathematical) based on the gender of the students, but there were significant differences in the level of naturalist intelligence in learning physical education for elementary schools based on the gender of the students.